Hepatoprotector Effect of Banana Peel (Musa paradisiaca Sapientum) on Paracetamol Induced Rats: Efek Hepatoprptektor Kulit Pisang Raja pada Tikus Yang Diinduksi Parasetamol - Jastria Pusmarani; Mus Ifaya; Risky Juliansyah Putri (Universitas Tadulako, 2022)
Background: Liver disease is generally still a high prevalence in Indonesia. One of drug-induced liver injury is paracetamol. Banana peel (Musa paradisiaca Sapientum) has flavonoid compounds that could increasing the production of glutathione enzymes in the liver. Objectives: This research aims to determine the activity of banana peel induced by paracetamol. This research is an experimental with pre and post test control group design method. Material and Methods: This research is an experimental with pre and post test control group design method. Group I was given 0.05% Na CMC as negative control, group II was given paracetamol 180 mg/kgBB as induction control group, group III was given banana peel extract at dose 700 mg / kgBB, group IV was given banana peel extract at dose 1400 mg/kgBB, and group V was given banana peel extract at dose 2100 mg/kgBW. Results: The liver damage can be measured by SGOT/SGPT serum levels of rats. SPSS data analysis with Paired sample T test obtained the value of p = 0.003 for SGOT (serum glutamic oxaloacetic transaminase) and p = 0.000 for SGPT. Conclusions: Both SGOT and SGPT values have p <0.05 which indicates that banana peel (Musa paradisiaca Sapientum) methanol extract has hepatoprotector effect on paracetamol-induced rats.